TOMATO (LYCOPERSICUM ESCULENTUM MILL.) RESILIENCE ENHANCEMENT WITH INDIGENOUS ENDOPHYTIC BACTERIA AGAINST BEMISIA TABACI (HEMIPTERA: ALEYRODIDAE) - H. Hamid; Y. Yanti; F. R. Joni; Nurbailis (Journal of Animal and Plant Sciences, 2020)
The use of indigenous endophytic bacteria (IEB) isolates as PGPR and resistance induction has been conducted to wilt in tomatoes (Lycopersicum esculentum Mill). This study aimed to obtain the best endophytic bacteria isolates in increasing the resistance of tomato plants to B. tabaci. The research used a completely randomized design (CRD) with ten treatments and three replications. The treatment consisted of eight isolates of IEB, positive controls (without using insecticides), and negative controls (using insecticides). The study was conducted at the Microbiology and Greenhouse Laboratory, Faculty of Agriculture, Universitas Andalas from May to July 2018. The parameters observed were the number of individuals who survived per day and the length of days needed to develop per stage. The results showed that EPL 1.1.4 and KLE 3.3 isolates inhibited egg laying, whereas EI.AB 2.1, EI.AB 1.2, KLE 3.3, and SNE 2.2 inhibited the development of B. tabaci. There was no difference in the length of day between IEB isolates and controls. EI.AB 2.1 showed the most significant adverse effect on the success of B. tabaci life with a value of lx = 0.0 achieved on nymph of instar 3. The result indicated that IEB could be developed in increasing the tomato plants resistance to B. tabaci.
Keywords: Bemisia tabaci; development stage; endophytic bacteria; resistance; tomato